Eugenia calycina Cambess extracts and their fractions: Their antimicrobial activity and the identification of major polar compounds using electrospray ionization FT-ICR mass spectrometry - Ferreira, Fernanda P. S.; Morais, Sandra R. [UNESP]; Bara, Maria T. F.; Conceicao, Edemilson C.; Paula, Jose R.; Carvalho, Thays C.; Vaz, Boniek G.; Costa, Helber B.; Romao, Wanderson; Rezende, Maria H. (Elsevier B.V., 2014)
Eugenia calycina, which is described as "red pitanga or pitanga cherry of cerrado," is widely distributed in the Cerrado area of Brazil. Its leaf and bark extracts are used in folk medicine for many applications. In this study, the compositions of the major polar compounds of the bark and leaf extracts and their fractions were obtained from a liquid-liquid extraction using hexane, dichloromethane, ethyl acetate, and water. They were then evaluated using electrospray ionization negative FT-ICR mass spectrometry (ESI(-) FT-ICR MS), which revealed a large number of oxygen-containing compounds, such as flavonoids, terpenes, tanins, steroids, and fat acids. The biological activity of these extracts towards several bacterial and fungal strains was then evaluated. The highest activity was found using aqueous fractions, in which the ESI(-) FT-ICR MS analysis revealed compounds with a high content of oxygen (e.g., glycosed flavonoids, tannins, and polyphenolic compounds) against Cryptococcus sp. D (minimum inhibitory concentration [MIC] = 15.62 mu g/mL). Strong activity was also found using the hexanic fractions-in which the ESI(-) FT-ICR MS analysis revealed that the compounds contained a decreased amount of oxygen (e.g., fat acids and steroids)-towards Cryptococcus gatti L48, Oyptococcus neoformans L3 (MIC = 31.2 mu g/mL), and Cryptococcus sp. D (MIC= 62.5 mu g/mL). Therefore, antimicrobial assays using the bark/leaf extracts of E. calycina present prospects for the research of active substances that may be used for the treatment of cryptococcosis, a disease that is common in immunosuppressed patients. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Eugenia calycina; Antimicrobial activity; ESI; FT-ICR MS; Myrtaceae, Medicinal plants